Discovery of novel 2′, 4′-dimethyl-[4, 5′-bithiazol]-2-yl amino derivatives as orally bioavailable TRPV4 antagonists for the treatment of pain: Part 1. Issue 20 (15th October 2016) - Tsuno, Naoki; Yukimasa, Akira; Yoshida, Osamu; Ichihashi, Yusuke; Inoue, Takatsugu; Ueno, Tatsuhiko; Yamaguchi, Hiroki; Matsuda, Hidetoshi; Funaki, Satoko; Yamanada, Natsue; Tanimura, Miki; Nagamatsu, Daiki; et al.
Graphical abstract: Abstract: A novel series of 2′, 4′-dimethyl-[4, 5′-bithiazol]-2-yl amino derivatives were found by high throughput screening of the TRPV4 receptor, at which these compounds showed competitive antagonist potential against 4α-phorbol 12, 13-didecanoate (4αPDD) as the selective TRPV4 agonist and showed excellent selectivity for TRPV1, N-type and L-type calcium ion channels, but poor ADME profile. In our SAR strategy, we found that the lead molecule1 also having the unique 3-oxa-9-azabicyclo [3.3.1] nonan-7-one on the right part showed potent TRPV4 antagonist activity, good solubility at pH 6.8, good microsomal stability for human and better ADME profile including oral bioavailability. Moreover, compound1 had an analgesic effect in Freund's Complete Adjuvant (FCA) induced mechanical hyperalgesia model in guinea pig. In this letter, we report a lead optimization process to identify the lead compound1 (Fig. 1).